How the world listens : the human relationship with sound across the world - Garner, Tom (Tom Alexander) (Routledge, 2023)
"How the World Listens explores our everyday and professional interactions with sound. The book aims to uncover the human relationship with sound across the world and to reveal practical ways in which a better understanding of listening can help us in our daily lives. This book asks how sound is perceived, expressed and interacted with in both remarkably similar and dramatically different ways across the world. Using findings from a new scientific study, conducted exclusively for this book, we embark on a globe-trotting adventure across more than thirty countries, through exclusive interviews with more than fifty individuals from all walks of life; from acousticians and film composers, to human resource managers and costumiers. How the World Listens is essential reading for anyone with an interest in human relationships with sound, including but not limited to sound design and music composition professionals, teachers and researchers"--